2013
DOI: 10.1016/j.ajog.2012.12.020
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of perinatal depression and trauma history in pregnant minority adolescents

Abstract: OBJECTIVE Adolescent pregnancy is common and minority adolescents are at high risk. We sought the following: (1) to prospectively assess prevalence of antenatal depression (AND) and postpartum depression (PPD) in minority adolescents and (2) to examine the association of social support and adjustment, trauma, and stress on depression status. STUDY DESIGN A total of 212 pregnant adolescents were recruited from public prenatal clinics and administered a prospective research survey during pregnancy and 6 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 42 publications
2
74
0
3
Order By: Relevance
“…In particular, childhood sexual abuse and emotional abuse were associated with both depression and PTSD, while childhood physical abuse was associated only with PTSD. These associations during pregnancy, novel to the South African context, expand the research base from developed settings in which early maltreatment has been found to be a risk factor for mental disorders in the perinatal period (Benedict, Paine, Paine, Brandt, & Stallings, 1999; Huth-Bocks et al, 2013; Kulkarni, Graham-Bermann, Rauch, & Seng, 2011; Meltzer-Brody et al, 2013). A history of childhood trauma may predict antenatal mental health in various ways.…”
Section: Discussionmentioning
confidence: 62%
“…In particular, childhood sexual abuse and emotional abuse were associated with both depression and PTSD, while childhood physical abuse was associated only with PTSD. These associations during pregnancy, novel to the South African context, expand the research base from developed settings in which early maltreatment has been found to be a risk factor for mental disorders in the perinatal period (Benedict, Paine, Paine, Brandt, & Stallings, 1999; Huth-Bocks et al, 2013; Kulkarni, Graham-Bermann, Rauch, & Seng, 2011; Meltzer-Brody et al, 2013). A history of childhood trauma may predict antenatal mental health in various ways.…”
Section: Discussionmentioning
confidence: 62%
“…6,31 Participants described complex trauma histories including child maltreatment, abandonment, assault, interpersonal violence, and traumatic loss. Clinicians should not underestimate the relevance and potential interconnection of adolescent women’s trauma history with their pregnancies, depression, and service experiences.…”
Section: Discussionmentioning
confidence: 99%
“…25 Estimated rates of pregnant adolescent women with PND, ranging from 20–44%, are 2 and 4 times the rate of low-income women and middle-class women, respectively. 68 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ELS is associated with higher infant cortisol reactivity, more negative emotionality (Feldman et al, 2009), and deficient OT signaling in social interactions (Wismer Fries et al, 2005). Importantly, effects of ELS-exposure may be long lasting and are reliable predictors for later life MDD (Heim and Binder, 2012), PPD (Meltzer-Brody et al, 2013), dysregulated HPA axis reactivity (Heim et al, 2008), as well as lower CSF (Heim et al, 2009) and plasma (Opacka-Juffry and Mohiyeddini, 2012) OT concentrations. This co-occurrence of ELS-dependent alterations begs the question of whether abnormalities in bi-directional OT-HPA-axis communication may critically shape the relationship between ELS and psychiatric risk in adulthood.…”
Section: Ot and Early-life Stress (Els) – Role In Shaping Neural Cmentioning
confidence: 99%